Heat transfer enhancement by tapered twisted tape inserts - Piriyarungrod, N.; Eiamsa-ard, S.; Thianpong, C.; Pimsarn, M.; Nanan, K. (My University, 2015)
The effects of inserted tapered twisted tapes, their taper angle and twist ratio on heat transfer rate, pressure drop and thermal performance factor characteristics have been reported. The experiments were carried out by using the tapered twisted tapes with 4 different taper angles which θ= 0.0° (typical twisted tape), 0.3°, 0.6° and 0.9°. At each taper angle, the tapered twisted tapes were twisted at three different twist ratios (y/W) of 3.5, 4.0 and 4.5. All tapes were tested under turbulent flow regime for Reynolds numbers between 6000 and 20,000. A twist ratio is defined as the ratio of twist length (y) to twisted tape width at the large end (W). The plain tube was also tested for comparison. Heat transfer enhancement and friction loss increased with decreasing taper angle and twist ratio. Thermal performance factor tended to increase with increasing taper angle and decreasing tape twist ratio. For the present range, the tube with the tape with taper angle (θ) of 0.9° and twist ratio (y/W) of 3.5 yielded the maximum thermal performance factor of 1.05 at Reynolds number (Re) of 6000.
Keywords: Heat exchanger; Heat transfer enhancement; Swirl flow; Tapered twisted tape